Changes in the technical readiness of volleyball players 10-11 years under the influence of visual perception of movement parameters - Strelnykova, I.; Gorchanyuk, Y.; Nesen, O. (Slobozhanskyi herald of science and sport, 2018)
Purpose: increase in the level of technical preparedness of volleyball players at the stage of initial training under the influence of visual perception of the parameters of movements.